A Discourse Analysis of German Fairy Tale â€œRapunzelâ€ Written by the Brothers Grimm (Language Circle: Journal of Language and Literature, 2018)
The objectives of this study are to describe the kinds of information in Rapunzel and to describe deixis, grammatical and lexical cohesion of Rapunzel. This study belonged to the qualitative study that was focused on the concrete phenomenon of the written materials. The technique of data collection was the writer observing the features that occur in the fairy tale then taking it to note. The writer found that: (1) title can be expounded by a short clause, phrase, or sentence, (2) the aperture is expounded by a clause, sentence, or paragraph, (3) the stage is expounded by a sentence or paragraph containing descriptive clauses, clauses with past completed action and identification clauses or noun phrase, (4) the author used third person pronouns she and he; (5) some nouns or pronouns were omitted in the second of coordinate clauses; (6) there were 64 sentences used additive conjunction and 10 sentences used comparative conjunction but, however, the conjunction neitherâ€¦nor, or and if is only used once; (7) the authors only repeated the words will and hair; (8) the authors used words bird and cat in which they are a hyponym of animal; and (9) the synonyms words are grief, misery, heard, listen.